A communications intervention to motivate disaster risk reduction. Issue 3 (6th June 2016) - Sanquini, Anne M.; Thapaliya, Sundar M.; Wood, Michele M.
Abstract : Purpose: – The purpose of this paper is to apply social theory to the creation of a mass-media communications intervention designed to encourage earthquake-resistant construction in Nepal. Design/methodology/approach: – A three-step process was employed in this study: first, a narrative literature review was completed regarding the motivation of protective action. Second, key informant elicitation interviews with 15 community members at five public schools who supported making their buildings earthquake-resistant informed the script for a documentary film. Finally, the film was reviewed with stakeholders, plus 16 community members associated with a school in need of seismic work. Sociograms were used to determine relative closeness of the study participants to the film role models. Findings: – Motivating factors identified in the literature synthesis were included in the film, which focussed on effective actions taken by role models, and avoided the use of fear-based appeals. Key informant interviews yielded role-modeling details for the film script, including triggers and obstacles faced by the community members, and outcomes of their actions. Sociogram outcomes guided film editing and increased relative screen time for those community members with whom the study participants felt greater closeness. A pretest-posttest cluster randomized trial (details reported elsewhere) showed greater gains in knowledge, perceived outcome effectiveness, and intended behaviors among intervention film viewers than control participants. Originality/value: – This three-step process yielded the information required by a practitioner to develop a theory-based, culturally appropriate mass-media intervention designed to motivate reduction of disaster risk.